Civil society: concepts, challenges, contexts: essays in honor of Helmut K. Anheier - Hölscher, Michael; List, Regina A.; Ruser, Alexander; Toepler, Stefan (Springer, 2022)
Chapter 1: Civil Society Concepts, Challenges, and Contexts: An Introduction to Helmut Anheier’s Festschrift -- Chapter 2: Scholarship, Leadership, and Institution Building: Helmut Anheier and the Nonprofit and Philanthropic Sectors -- Part I: Developing Concepts and Theoretical Frames -- Chapter 3: The Theory of the Public Sphere Revisited -- Chapter 4: Dealing with Civility: Citizenship, Real Citizens and the Science of Civil Society -- Chapter 5: Successful Failure: Functions and Dysfunctions of Civil Society Organizations -- Chapter 6: Social Innovation – Not Without Civil Society -- Chapter 7: The Hiding Hand, Persistent Fragile Action, and Sustainable Development -- Chapter 8: Using the System of National Accounts Framework to Measure Social Impacts of Social Economy Institutions -- Chapter 9: From Anheier’s Civil Society Diamond to a Principled Fundraising Jurisprudence for Civil Society -- Chapter 10: Legitimizing Foundations: Functions, Expectations, and Regulation -- Chapter 11: Foundations and Democracy: The Changing Case for the Defense -- Chapter 12: Foundations: Is Measurement the Enemy of Creativity -- Part II: Charting Global Challenges -- Chapter 13: Planetary Politics: Reviving the Spirit of the Concept “Global Civil Society” -- Chapter 14: Global Civil Society in Retreat: Is It Cyclical or Existential -- Chapter 15: The Offensive Against Global Civil Society: Diffusion of NGO Restrictions -- Chapter 16: Civil Society Actors in International Cultural Diplomacy -- Chapter 17: Arts, Cultural Participation, and Democracy. Analyzing the Indicator Framework on Culture and Democracy -- Chapter 18: Global Civil Religion -- Chapter 19: Civil Society and the Problem of Knowledge -- Chapter 20: The Dark Side of the Nonprofit Sector: Polarization in Contemporary Society -- Part III: Changing Contexts: Local and Regional Case Studies -- Chapter 21: Civil Society Encroachment in Non-liberal Democracies: The Case of Israel -- Chapter 22: Policy Controversies and Challenges for Organized Civil Society: The Case of England Before the COVID-19 Crisis -- Chapter 23: Transformation of Civil Society Organization Functions in Modern Russia -- Chapter 24: The Skeptic Who Came in from the Cold? The Formation of a Climate-skeptic Alliance in Germany -- Chapter 25: The Recent Evolution of Foundations in France -- Chapter 26: Pluralism and Inequality: Brief Reflections on Philanthropic Foundations and their Study in the United States -- Chapter 27: Businesses as Civil Society Actors? An Engagement and Cooperation Analysis Based on German Company Data -- Chapter 28: Scenarios for Civil Society Impact in Norway -- Chapter 29: Women in the German Nonprofit Sector: Working Conditions and Promotion Opportunities -- Chapter 30: Los Angeles and the State of the Nonprofit Sector: A Review of Findings and Examination of Three Theses -- Appendix: Helmut K. Anheier’s publications -- Index.
Keywords: Aufsatzsammlung; Festschrift; Zivilgesellschaft